MULTIMEDIA PEMBELAJARAN IPS MATERI KONDISI GEOGRAFIS WILAYAH INDONESIA PADA SISWA KELAS V SEKOLAH DASAR - Irmawati Irmawati; I Nyoman Sudana Degeng; Ery Tri Djatmika (Graduate School of Universitas Negeri Malang, 2017)
The Research aimed at producing multimedia learning material IPS geographical condition of Indonesia in fifth grade elementary school students who meet the eligibility terms of validity, practicability, the attractiveness and effectiveness. This study is a Research & Development (R & D) with a model of the development of Lee & Owens (2004) with the systematic stages. The stages are analysis, design, development, implementation and evaluation. The results showed the level of validity 87.92%, 92.47% rate of practicality, the attractiveness of the level of 93.57% and 90.90% level of validity. Advice from experts and users into consideration in the improvement of the product so that the product be fit for use.Penelitian ini bertujuan menghasilkan multimedia pembelajaran IPS materi kondisi geografis wilayah Indonesia pada siswa kelas V sekolah dasar yang memenuhi kelayakan dari segi kevalidan, kepraktisan, kemenarikan dan keefektifan. Penelitian ini merupakan penelitian Research & Development (R&D) dengan model pengembangan Lee & Owens (2004) dengan tahapan yang sistematis, yaitu tahap analisis, desain, pengembangan, implementasi dan evaluasi. Hasil penelitian menunjukkan tingkat kevalidan 87,92%, tingkat kepraktisan 93,56%, tingkat kemenarikan 93,59% dan tingkat kevalidan 90,90%. Saran dari para ahli dan pengguna menjadi pertimbangan dalam perbaikan produk sehingga produk menjadi layak digunakan.